Is policy of memory possible and how? - Kowalska, Wioletta Małgorzata (Creativity Studies, 2008)
The purpose of this paper is to discuss the concept and possibility of the democratic policy of collective memory in national and trans‐national, or European, contexts. The presupposition of the paper is that memory, while largely unintentional, is also intentional and even partially constructed and, as such, always subjected to influences, even manipulations, i.e. to different policies. Memory is no doubt a “political question” and every policy deals with it, trying to shape social memory according to some political and ideological objectives. In particular, communism implied a very strong policy of memory aiming at destroying many sorts and layers of memory in favour of another. After the fall of communism there have also been many attempts at reshaping collective memory. These recent attempts have been certainly much more democratic than the communist manipulations but far from being based on the democratic principle of equality of different perspectives and discussion. The attempt was rather, namely in Poland, to replace, once again, one kind of “official” memory by another. The really democratic policy of collective memory should imply, on the contrary, a free confrontation of different and sometimes opposing memories in the open public sphere where no “symbolic violence” has place and where all participants not only treat each other as equals but are also ready to modify the meaning of their particular memory and look for mutual comprehension, if not for agreement. The question is whether such democratic policy can ever be more than a moral postulation. Ar įmanoma atminties politika ir kaip? Santrauka. Aptariamas demokratinės politikos ir kolektyvinės atminties santykis bei jo galimybės sąlygos nacionaliniame ir transnacionaliniame (europiniame) kontekste. Teigiama, kad nesąmoninga atmintis neišvengiamai priklausoma nuo tam tikrų įtakų ir net manipuliacijų, t. y. nuo skirtingų politinių pažiūrų. Atmintis neabejotinai esanti tam tikras „politinis klausimas“, į kurį skirtingų politinių pažiūrų atstovai bando skirtingai atsakyti, bandydami socialinę atmintį apibrėžti, vedini savųjų politinių ir ideologinių tikslų. Komunizmo išpažinėjai siekė sunaikinti kolektyvinę atmintį, siekdami įvairios politinės naudos. Žlugus komunizmui buvo stengiamasi iš esmės atgaivinti kolektyvinės atminties fenomeną. Šiandienės pastangos tai padaryti esančios kur kas demokratiškesnės negu komunistų vykdytos manipuliacijos, tačiau vargu ar pagrįstos skirtingų politinių pažiūrų lygiavertiškumo ir demokratijos principais. Demokratinė politika turėtų užtikrinti laisvą skirtingų, o kartais net ir prieštaraujančių tarpusavyje atminties rūšių koegzistavimą viešosiose srityse, kuriose nebūtų jokių „simbolinės prievartos“ apraiškų, o visi visuomenės nariai turėtų lygias pilietines teises siekdami abipusio supratimo ir tarpusavio sutarimo. Pasak autorės, net šiandien tenka kelti klausimą – ar demokratinė politika gali pretenduoti į aukštesnį nei moralinio postulato statusą? Reikšminiai žodžiai: konsensas, disensas, demokratija, atmintis, politika, valdžia, simbolinė prievarta, universalizmas, reliatyvizmas. First Published Online: 14 Oct 2010